The management of bank funds - Robinson, Roland I. (New York : McGraw-Hill, 1951)
Many of the traditions of banking are entirely oral passed along by word of mouth and seldom written down. This book proposes to put this oral tradition in writing.
Includes index
usc 16/05/2017
Loans
Keywords: Banks and banking